Analisis Soft Skill dan Kesiapan Memasuki Dunia Kerja Siswa Bidang Teknologi dan Kejuruan SMKS Semen Padang - Refi Habibullah Karim; Rizky Ema Wulansari; Mulianti Mulianti; Fitrah Qalbina (TSAQOFAH, 2026)
Work readiness among technology and vocational students is determined not only by mastery of technical competencies but also by soft skills that support adaptation, collaboration, and professionalism in the workplace. This study aims to analyze the level of soft skills, work readiness, and the relationship between the two among technology and vocational students at SMKS Semen Padang. This study used a descriptive quantitative approach with a correlational design. The research population consisted of students in Grades XI and XII, with a sample of 59 respondents selected using proportional random sampling. Data were collected using a Likert-scale questionnaire that had been declared valid and reliable. Data analysis techniques included descriptive statistics, normality testing, linearity testing, and Pearson correlation analysis. The results show that students’ soft skills were in the very good category, with an average percentage of 81.94%. The most dominant aspect was creativity and problem solving, followed by teamwork, time management, leadership, work ethics, and communication. Students’ work readiness was in the very ready category, with a percentage of 85.63%. In addition, there was a very strong positive and significant relationship between soft skills and work readiness, with a Pearson correlation coefficient of 0.988 (p < 0.05). The conclusion of this study emphasizes that soft skills are strongly associated with vocational high school students’ readiness to enter the workforce. These findings imply the importance of strengthening learning based on soft skill development in vocational education so that graduates are better prepared to meet the demands of the workforce.